An optical sensor based on immobilized copper(II) ions for the determination of free glutamate in food samples - Md Muslim N.Z.; Ahmad M.; Heng L.Y.; Saad B. (Penerbit Universiti Kebangsaan Malaysia, 2024)
An optical fiber chemical sensor for the determination of free glutamate in food samples was fabricated based on the immobilization of 0.1 M copper(II) nitrate trihydrate onto sol-gel glass powder which was then mixed with methyl cellulose to form a pellet. A distinctive colour change from light blue to dark blue was observed in the presence of glutamate in less than 1 min. The colour change was measured by reflectance spectrophotometer at 691 nm. A linear relationship between the reflectance intensity and glutamate concentration was observed in the range of 12.5 to 500 mM with a limit of detection of 10.6 mM. This method is also reproducible with a relative standard deviation of less than 5%, no effect on pH of the glutamate solution and a good recovery of above 80%. The sensor was used for the determination of glutamate in common food items such as soups and flavor enhancers. The results obtained from the fabricated sensor were found to be comparable with HPLC method.